A randomized controlled trial for effectiveness of zolpidem versus acupressure on sleep in hemodialysis patients having chronic kidney disease–associated pruritus - Rehman, Inayat Ur; Chia, David Wu Bin; Ahmed, Raheel; Khan, Nisar Ahmad; Rahman, Aziz Ur; Munib, Syed; Lee, Learn Han; Chan, Kok Gan; Khan, Tahir Mehmood (Lippincott, Williams & Wilkins, 2018)
BACKGROUND: Pruritus adds to the complications of chronic kidney disease (CKD) patient and a well-recognized complication among the CKD patients. Majority of the patients on hemodialysis experience a generalized pruritus and patients reported being moderately to extremely disturbed by at least one of the sleep-related condition. This study aim to investigate the effectiveness of zolpidem 10 mg and acupressure therapy on foot acupoints to improve the sleep quality and overall quality of life among hemodialysis patients suffering from CKD-associated pruritus.